ALUN – ALUN PURWOKERTO : DARI HALUN – HALUN KE OPEN SPACE - Wita Widyandini (Fakultas Teknik Universitas Wijayakusuma Purwokerto, 2012)
ALUN – ALUN PURWOKERTO :DARI HALUN – HALUN KE OPEN SPACE Oleh : Wita Widyandini ABSTRACTThe town square existence in a town or a regency in Java, is an identity that shows the typical and uniqueness of that city or regency. The town square is the spatial structure binding between the power holder (Royal Palace or regency building), mosque, jail, or the settlement around that own town square. Traditional town square with its Ringin Kurung is an example of an opened space full with various functions and deeply meaning. However, as the development and the demands of the times, there are many town squares in Java that needs to be renovating. As the result, there are town squares remain with its genuine meaning, but some of them has lost its meaning as a town square, changes into just an opened town space.Keywords : alun-alun, halun-halun, open space